Exploring community pharmacists’ communication on the use of emergency contraceptive pills to customers - Leiu, Chang You (2020)
Premarital sex is increasingly common among the youth in Asian countries. This entailed the emergence of increase use of emergency contraceptive pills (ECP) among young female adults. In Malaysia, premarital unplanned pregnancy is evident with low awareness and knowledge of contraception. However, pharmacists constantly ensure ECP users received education on top of the medication. This study focused into the education and communication process of ECP information transition from pharmacists to consumers by understanding the current practices implemented and considering the challenges and cultural aspects in Malaysia context. Eventually, exploration of a communication material which can improve the education and communication process of ECP awareness and use to reduce risk of unwanted pregnancy. This thesis explored community pharmacists’ perspectives on a communication material for pharmacists during ECP counselling to young female adults in Malaysia. Eleven (11) interviews were conducted with purposive sampling until data saturation was achieved. All audio-recorded interview sessions were transcribed verbatim and analysed thematically using the NVivo 10 software (QSR, Melbourne). Themes emerged from the current pharmacist’s practice in communicating ECP use to young female adults were: (1) pharmacist’s approach to initiate in-depth counselling with young female adults, (2) gathering of information from young female adults, and (3) content of in-depth counselling given to young female adults. Themes which emerged from the challenges encountered by pharmacists when communicating ECP to young female adults and how they manage these challenges were: (1) perceived attitude among young female adults in seeking ECP, (2) environmental setting in community pharmacy, and (3) ECP supporting communication tools for pharmacists. Lastly, themes generated from types of effective communication channels and why are the suggested communication channels are potential to deliver ECP information to young female adults as perceived by pharmacists were: (1) varying communication channels, (2) layout of printed communication materials, and (3) content in a communication material. Findings from this study revealed that participants generally valued the use of communication material in guiding face-to-face communication of ECP counselling session. Together with face-to-face communication, printed ECP leaflet is particularly useful to overcome challenges faced by pharmacists in Malaysia. With these communication channels, quality patient education could be accomplished followed by improved contraception outcomes. The findings of this study will contribute as a foundation in commercialising the communication material by putting it into practice.